The Influence of Service Quality and Sales Promotion on Repurchase Intention through Customer Satisfaction as an Intervening Variable (A Case Study on Guardian Consumers in the Greater Bekasi Area) - Kusumaningrum, Nadila; Sadat, Andi Muhammad; Monoarfa, Terrylina Arvinta (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The increasing competition in Indonesia’s health and beauty retail sector has raised concerns regarding inconsistent service quality and promotional discrepancies that negatively impact customer trust and loyalty. This study aims to examine the influence of service quality and sales promotion on repurchase intention, with customer satisfaction as a mediating variable. The research focuses on Guardian retail consumers in the Greater Bekasi area. Employing a descriptive quantitative approach, data were collected from 200 respondents using a convenience sampling technique and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that both service quality and sales promotion significantly and positively affect customer satisfaction and repurchase intention. Furthermore, customer satisfaction plays a mediating role in the relationship between service quality, sales promotion, and repurchase intention. These findings highlight the critical role of customer experience in strengthening repurchase behavior and suggest that companies should invest in improving both service quality and promotional strategies to foster customer loyalty in a competitive retail landscape.